2014
DOI: 10.4103/0973-1482.151542
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic value of endorectal ultrasonography for rectal carcinoma: A meta-analysis

Abstract: ERUS was a good method for the assessment of invasion of rectal tumors and lymph node involvement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 11 publications
0
3
0
1
Order By: Relevance
“…It is difficult to differentiate between benign and malignant lymph nodes using ERUS 35 , even for experienced users. Moderate sensitivities (57–73%) and specificities (76–80%) have been reported by several meta-analyses 26 36 37 38 . However, none of the currently available imaging methods (MRI and CT) can provide more reliable information on lymph node status 38 .…”
Section: Endorectal Ultrasoundmentioning
confidence: 90%
See 1 more Smart Citation
“…It is difficult to differentiate between benign and malignant lymph nodes using ERUS 35 , even for experienced users. Moderate sensitivities (57–73%) and specificities (76–80%) have been reported by several meta-analyses 26 36 37 38 . However, none of the currently available imaging methods (MRI and CT) can provide more reliable information on lymph node status 38 .…”
Section: Endorectal Ultrasoundmentioning
confidence: 90%
“…Studies available from the literature have reported very good performance of ERUS regarding the pre-therapeutic assessment of the depth of tumor invasion, with sensitivities and specificities ranging between 80–96%, and 80–98%, respectively, as shown by meta-analyses 25 26 . ERUS is the best documented examination for classifying early rectal lesions 27 , either confined to the mucosa (sensitivity and specificity ~ 97%) which may be referred for endoscopic resection ( Fig.…”
Section: Endorectal Ultrasoundmentioning
confidence: 96%
“…However, the implementation of abdominal computed tomography (CT) scan showed clear images of the local spread of distal rectal cancer, where the exact relation between the tumor and surrounding organ used to be unclear [ 4 ]. The endorectal ultrasonographic evaluation was later available, easy to use, and helpful to assess the depth of invasion [ 5 ]. However, its use was limited and operator-dependent, and in some cases, not able to evaluate the complete extension of the tumor above the anal sphincter and levator ani complex.…”
Section: Introductionmentioning
confidence: 99%
“…Apesar do ultrassom ser capaz de determinar características sugestivas de malignidade, como formato arredondado, localização peritumoral, tamanho (> 5 mm) e hipoecogenicidade heterogênea, esses fatores parecem não ser suficientemente sensíveis ou específicos para o diagnóstico correlato de malignidade com o espécime cirúrgico (50,57,58) . (62) .…”
Section: Decisão Terapêuticaunclassified